How practice nurses engage with parents during their consultations about the MMR vaccine: a qualitative study. (27th May 2021) - Hill, M.C.; Salmon, D.; Chudleigh, J.; Aitken, L.M.
Abstract: Aim: We aimed to understand practice nurses' perceptions about how they engage with parents during consultations concerning the measles, mumps and rubella (MMR) vaccine. Background: The incidence of measles is increasing globally. Immunisation is recognised as the most significant intervention to influence global health in modern times, although many factors are known to adversely affect immunisation uptake. Practice nurses are a key member of the primary care team responsible for delivering immunisation. However, little is known how practice nurses perceive this role. Methods: Semi-structured interviews were undertaken with 15 practice nurses in England using a qualitative descriptive approach. Diversity in terms of years of experience and range of geographical practice settings were sought. These interviews were recorded, transcribed verbatim and open-coded using qualitative content analysis to manage, analyse and identify themes. Findings: Three themes were derived from the data: engaging with parents, the informed practice nurse and dealing with parental concerns: strategies to promote MMR uptake. During their consultations, practice nurses encountered parents who held strong opinions about the MMR vaccine and perceived this to be related to the parents' socio-demographic background. Practice nurses sought to provide parents with tailored and accurate sources of information to apprise their immunisation decision-making about the MMR vaccine.